The new economic governance framework of the European Union - Ioana - Sorina Mihuț (CES Working Papers, 2018)
There is a general agreement that the European Union is facing nowadays one of the most important challenges in the history of the community, taking into consideration the wide range of economic, social and political risks that constitute top priorities of the European authorities. One key concept in this approach is the efficiency of the economic governance process. The main purpose of this article is to evaluate the ability of the European Union to elaborate sound policies in the current economic framework that are focusing on supporting the common interests of all the Member States, with particular focus on the economic governance process. Furthermore, the article targets at identifying whether or not the new architecture of the EU economic governance developed as a result of the 2008 financial crisis constitute a triggering factor for social cohesion and political harmonization across the European community.
Keywords: H11; O38; O43; 330; Economic governance; macroeconomic policies; economic governance; government quality; institutions